Cationic amphiphiles against Gardnerella vaginalis resistant strains and bacterial vaginosis-associated pathogens. Issue 8 (11th October 2019) - Weeks, Richard M; Moretti, Alysha; Song, Shuang; Uhrich, Kathryn E; Karlyshev, Andrey V; Chikindas, Michael L
ABSTRACT: Antibiotic resistance and infection recurrence are critical issues in treating bacterial vaginosis, the most common vaginal disorder in women of reproductive age. Novel alternatives to traditional antibiotics, such as peptidomimetics, have the potential to address this challenge. Previously, two series of cationic amphiphiles (CAms) were developed with both hydrophilic head groups and non-polar domains, giving them the ability to self-assemble into supramolecular nanostructures with membrane-lytic properties. Those CAms were shown to be effective against biofilms of Gardnerella vaginalis while preserving the commensal microbiota. Two new series of CAms were designed with varying levels of flexibility between the hydrophilic head groups and the hydrophobic domains. Activities against the vaginal pathogen G. vaginalis ranged from 1.3 to 18.5 µM, while the tested vaginal lactobacilli were significantly more tolerant of CAms, with minimal inhibitory concentration values as high as 208 µM. Minimal biofilm bactericidal concentrations of the tested CAms ranged from 21.47 to <388.3 µM, and were lowest against resistant forms of G. vaginalis, while Lactobacillus biofilms were tolerant of concentrations ≥687 µM. Safety aspects of the CAms were also investigated, and they were found to be safe for use against vaginal ectocervical tissue. Abstract : Cationic amphiphiles control Gardnerella vaginalis .